2020
DOI: 10.3390/ma13214912
|View full text |Cite
|
Sign up to set email alerts
|

Pyrolysis of Mixed Plastic Waste: I. Kinetic Study

Abstract: Plastic wastes have become one of the biggest global environmental issues and thus recycling such massive quantities is targeted. Low-density polyethylene (LDPE), high-density polyethylene (HDPE), polypropylene (PP), and polystyrene (PS) are considered among the main types of plastic wastes. Since pyrolysis is one of the most promising recycling techniques, this work aims to build knowledge on the co-pyrolysis of mixed polymers using two model-fitting (Criado and Coats–Redfern) methods. Seventeen co-pyrolysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
35
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(41 citation statements)
references
References 30 publications
6
35
0
Order By: Relevance
“…Although Figure 1 represents data of the equi-mass binary mixture of PP and PS, Figure 2 shows the TGA data of the equi-mass ternary mixture of PP, PS, and LDPE at different heating rates. Generally, as reported for individual plastics in previous works [ 15 , 16 , 17 ], thermograms of all mixtures have a similar inverted S-shape. However, they were shifted to higher temperatures as the heating rate increased (i.e., a faster heating rate implies a small weight loss at specific temperatures).…”
Section: Resultssupporting
confidence: 77%
See 2 more Smart Citations
“…Although Figure 1 represents data of the equi-mass binary mixture of PP and PS, Figure 2 shows the TGA data of the equi-mass ternary mixture of PP, PS, and LDPE at different heating rates. Generally, as reported for individual plastics in previous works [ 15 , 16 , 17 ], thermograms of all mixtures have a similar inverted S-shape. However, they were shifted to higher temperatures as the heating rate increased (i.e., a faster heating rate implies a small weight loss at specific temperatures).…”
Section: Resultssupporting
confidence: 77%
“…Proximate and ultimate analysis was performed to characterize the polymer samples; these data are presented in Table 1 . Details of both tests are described elsewhere [ 15 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was observed that an increase of PP share caused a decrease of process temperature and losses yield, thus increasing product yield. This synergetic behaviour was in line with the findings of Dubdub and Al-Yaari for a batch process conducted in a thermogravimetric analyser (TGA) [ 47 ]. Surprisingly, the product yield in the process with Sample 5 was higher than for pure PP.…”
Section: Resultssupporting
confidence: 88%
“…al [10] built a mathematical model of single-particle biomass under the pyrolysis process and compared the results with experimental measurements and other different types of wood samples, the ultimate analyses for the composition have been reported. Dubdub and Al-Yaari [11] investigated the kinetics of mixed plastic waste. Their results showed that using a single thermal degradation stage, the pyrolysis of pure polymer samples happens in the following order: PS, PP, LDPE, and HDPE.…”
Section: Introductionmentioning
confidence: 99%